The NEMESIS Social Innovation Learning Platform - Protopsaltis, Aristidis; Copado Mejías, Jesús; Schorer, Antonia; Garefi, Ioana; Kalemaki, Irene (Proceedings of 11th International Social Innovation Research Conference, 2020)
This paper presents the NEMESIS Social Innovation Open Learning Platform (SIOLP) and its evaluation results during piloting in 5 European countries. The NEMESIS SIOLP is an open adaptive and evolving platform, based on ILIAS open source software, that ensures access to SI education for all. Existing educational programs on social innovation or on social entrepreneurship education are limited, while they cannot be accessed by all. Additionally , there is no platform that supports Social Innovation Education (SIE). The NEMESIS SIOLP offers the tools and resources to all teachers, trainers and educators around Europe to adopt the NEMESIS social innovation education model in an easy and effective way. The platform provides open access to useful resources for teachers but also an online knowledge sharing space for students. Particularly, For the evaluation of the NEMESIS SIOLP, a single-factor design has been used, using two different questionnaires during the pre-pilot evaluation. The System Usability Scale (SUS) developed by Brooke (1996) and the IsoMetrics usability inventory (Gediga, Hamborg & Düntsch, 1999). The SUS questionnaire was modified to include some more task specific questions to fit the NEMESIS tasks. The IsoMetrics usability inventory (Gediga, Hamborg & Düntsch, 1999) is a user-oriented approach to software evaluation and its short version was used. Additionally, a realistic approach was used during the pilot phase. A realistic approach to evaluation permits us to understand under what circumstances complex interventions work or fail (Pawson & Tilley, 2004). The results presented in this paper refer to the first complete evaluation of the “alfa” version of the system in 5 European counties and 8 schools. The survey was anonymous and the participants had to complete a set of tasks before they answered the questionnaire. The evaluation results have shown that the NEMESIS SIOLP largely supports the stakeholders' needs but usability issues were identified
Keywords: Social Innovation; Social Innovation Education; Open Learning Platform; Evaluation